Feminist Criminology (Archives of Criminology, 2014)
This article discusses the defining characteristics of feminist criminology. Given the sheer volume of materials and data on feminist criminology, I have selected only those aspects which I believe enable it to be described as completely as possible. The theoretical and methodological premises of feminist criminology are discussed first. The focus is on the key concepts and methodological research principles that distinguish feminist criminology from other trends in criminology. The existing literature on feminist criminology is then presented to show the extent to which the topic has been explored both empirically and theoretically. The diverse interests of feminist researchers, both male and female, are also apparent in the next aspect of feminist criminology, viz. the divisions and different strands of feminist thinking on criminology. Those that appear most frequently in the literature are discussed. The premises, areas and variants of feminist criminology have to be described before questions can be asked about its status and its future. The status and future of feminist criminology are, I believe, the two key components of any discourse on the feminist perspective. As such, they are discussed as well. The final aspect of feminist criminology is its definition. This is derived from the topics mentioned above.